Quantum-chemical calculation of modified iliconcontained zeolite clusters electronic structure by zinc and calcium ions - Pokhmurskii, Vasyl; Korniy, Sergiy; Kopylets, Volodymyr; Kosarevych, Bogdan (Publishing House of Lviv Polytechnic National University, 2014)
Geometrical and electronic structure of clinoptilolite clusters modified by zinc and calcium cations were calculated by semiempirical quantumchemical method PM6. The value of formation heat, potentials of ionization, EHOMO and ELUMO energies, cations and oxygen atoms charges, and also binding energy of cations with the cluster were obtained. The redistribution of electronic density on the oxygen atoms of clusters during formation of bonds with zinc and calcium cations was analyzed. The ability of modified clinoptilolite clusters to sorb the hydrogen ions has been estimated. It has been established that clinoptilolite clusters modified by calcium cations can inhibit corrosive processes on the metals surface. Із використанням напівемпіричного квантово-хімічного методу PM6 проведені розрахунки геометричної та електронної структури модифікованих кластерів клиноптилоліту катіонами кальцію та цинку. Отримано значення теплот утворення, потенціалів йонізації, енергій EHOMO та ELUMO, зарядів на катіонах та кислотних центрах, а також енергії зв’язків катіонів з кластером. Проаналізовано перерозподіл електронної густини на атомах кисню кластерів під час утворення зв’язків з катіонами цинку та кальцію. Проведено оцінку реакційної здатності модифікованих кластерів клиноптилоліту до сорбції йонів водню. Встановлено, що модифіковані кластери клиноптилоліту катіонами кальцію можуть сповільнювати корозійні процеси на поверхні металів.
Квантово-хімічний розрахунок електронної структури модифікованих кремнійвмісних цеолітних кластерів йонами цинку і кальцію
Keywords: quantum chemical approach; clinoptilolite cluster; electronic density; zinc and calcium cations; electronic structure; квантово-хімічний підхід; кластер клиноптилоліту; електронна густина; катіони цинку і кальцію; електронна структура